Information acquisition ahead of monetary policy announcements - Michael Ehrmann; Paul Hubert (European Central Bank (ECB), 2023)
How do financial markets acquire information about upcoming monetary policy decisions, beyond their reaction to central bank signals? This paper hypothesises that sharing information among investors can improve expectations, especially in the presence of disagreement or uncertainty about the economy. To test this hypothesis, the paper studies monetary policy-related content on Twitter during the "quiet period" before European Central Bank announcements, when policymakers refrain from public statements related to monetary policy. Conditional on large disagreement about the economic outlook, higher Twitter traffic is associated with smaller monetary policy surprises, suggesting that exchanging private signals among investors can help improve expectations.
Keywords: D83; E52; E58; G14; 330; Central bank communication; quiet period; Twitter; market expectations; information processing